BFG; A NOVEL WRITTEN BY ROAL DAHL HOW TO DEAL WITH THE CHARACTERIZATION IN TEACHING PROSE - Elisna Huan (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2020)
Using simple and interesting strategies in teaching Prose is a must for a lecturer. There are many new methods or strategies to be applied in our classroom when we teach our students the characterization theories, one of them is STEAL Strategy. It is basically the characterization theories that have been summed up into a mnemonic device in form of an acronym (Speech, Thought, Effect on Others, Action, Looks) to help our students to easily memorize something. This writing is trying to prove the effectiveness of the strategy when it is applied to a novel entitled BFG written by Roald Dahl. The results show that this strategy helped the writer in making inferences, finding specific textual evidence to support the assertion about the chosen character, and also developing arguments. Therefore, the writer would like to suggest the English Study Program lecturers who teach Prose or Extensive Reading to apply this method in his or her classroom.